DETERMINE COMPETENCES FOR A PHYSIOTHERAPY GRADE SUBJECT - Lara-Romero, M. F (Cuestiones de Fisioterapia, 2009)
Among the many challenges that adaptation to the European Framework of Higher Education entails, one main is to elaborate the programs around the student, fomenting its participation. In order to obtain it, the development of a competencies-based curriculum is necessary. The present article sets out to determine what competencies are adapted to comprise of the curriculum of a Degree of Physiotherapy’s subject. A questionnaire with a Likert type scale is elaborated and administered to the professors of the subject. According to its valuations, a listing of competencies adapted for the programming and the methodological development of the subject sets out.